Calvary and the church broken for the world. Issue 2 (19th June 2018) - Saler, Robert C.
Abstract: The film Calvary raises a host of issues around how the movie‐going public understands clergy. Perceptions of clergy are often caught between expectations of hypocrisy and accusations of naivety. By subverting any sharp distinctions between that which is "holy" and that which is fully human in the calling of the priest, the movie demonstrates a kind of cinematic Christology that is also instructive for ecclesiological purposes, particularly when put in dialogue with the theology of Dietrich Bonhoeffer on the same subject.